Minimizing Ecological Damage from Road Improvement in Tropical Forests - Dasgupta, Susmita (World Bank, Washington, DC, 2016)
A spatial econometric model is used to link road upgrading to forest clearing and biodiversity loss in the moist tropical forests of Bolivia, Cameroon, and Myanmar. Using 250-meter cells, the model estimates the relationship between the rate of forest clearing in a cell and its distance to the urban market, with explicit attention given to road quality and simultaneity, terrain elevation and slope, the agricultural opportunity value of the land, and its legal protection status. Forest clearing is found to be most responsive to the distance to the nearest urban market, especially with secondary roads with lower typical speeds. Using the estimated forest-clearing response elasticities and a composite biodiversity indicator, an index of expected biodiversity loss from upgrading secondary roads to primary status is computed in each cell. The results identify areas in the three countries where high expected biodiversity losses may warrant additional protection as road upgrading continues. In addition, the results provide ecological risk ratings for individual road corridors that can inform environmentally sensitive infrastructure investment programs.